ANALISIS KEKUATAN STRUKTUR SISTEM MEKANIK PESAWAT SINAR-X DIGITAL - Zayadi, Ahmad; sudi, Mar (JTK: JURNAL TEKNOLOGI KEDIRGANTARAAN, 2019)
Analysis of structural strength of mechanical systems on digital x-ray devices. This research is very important to know the strength and quality of the structure of mechanical system of digital x-ray plane. To research analysis strength structure system mechanical calculation methods were used counting stress, bending stress; the safety factor a tool, and calculate deflection occurring in structure.The result of his research or: the bending stress at order holders catcher of = 7,07 N/mm2, while the bending stress is equal to = 141,9 N/mm2. The bending stress on the tube holder is as big as = 7,8 N/mm2, while the bending stress is equal to= 141,9 N/mm2. Stress von mises in order arms part burden a counterweight of = 19,44 N/mm2, while the value of the safety factor is n = 11,05. Stress von mises in order to arms a part of encumbering tube = 18,41 N/mm2, while the value of the safety factor is n = 11,67. Bending stress happened to column of order = 22,60 N/mm2, while the bending stress is equal to = 141,9 N/mm2. The ball screw move of the operation Fbm = 777,9N. Bending stress occurred on the basis of order = 21,43 N/mm2, while the bending stress is equal to = 141,9 N/mm2. Based on the data has obtained, then structure mechanical system plane digital sinar-x expressed safe and strength.Analysis of structural strength of mechanical systems on digital x-ray devices. This research is very important to know the strength and quality of the structure of mechanical system of digital x-ray plane. To research analysis strength structure system mechanical calculation methods were used counting stress, bending stress; the safety factor a tool, and calculate deflection occurring in structure.The result of his research or: the bending stress at order holders catcher of = 7,07 N/mm2, while the bending stress is equal to = 141,9 N/mm2. The bending stress on the tube holder is as big as = 7,8 N/mm2, while the bending stress is equal to= 141,9 N/mm2. Stress von mises in order arms part burden a counterweight of = 19,44 N/mm2, while the value of the safety factor is n = 11,05. Stress von mises in order to arms a part of encumbering tube = 18,41 N/mm2, while the value of the safety factor is n = 11,67. Bending stress happened to column of order = 22,60 N/mm2, while the bending stress is equal to = 141,9 N/mm2. The ball screw move of the operation Fbm = 777,9N. Bending stress occurred on the basis of order = 21,43 N/mm2, while the bending stress is equal to = 141,9 N/mm2. Based on the data has obtained, then structure mechanical system plane digital sinar-x expressed safe and strength.